What are medical students' attitudes to clinical risk-scoring tools? An exploratory study. Issue 6 (2nd November 2019) - Tomlinson, Fiona; Willis, Thomas A
ABSTRACT: Background: Clinical risk-scoring tools are increasingly recommended for use in general practice. Yet adoption of the tools has been variable and often low. Reasons for this have been explored, but medical students' perspectives have not previously been sought. Aim: To explore medical students' attitudes towards clinical risk-scoring tools. Methods: Qualitative, semi-structured interviews were conducted with eight medical students. Interviews were recorded, transcribed and analysed thematically. Results: Participants had a good understanding of the use of risk-scoring tools. They would trust them to enable evidence-based practice provided they are easy to use, not time-consuming and their results can help direct management. They were considered useful tools, especially for students and junior doctors. However, many believed the tools hold less value for experienced doctors. Their attitudes seem to have developed from discussions with clinicians, observation on placement, teaching received and exam content. Conclusion: This research recommends that implementation of risk-scoring tools will be increased if they are easier to use and if the belief that they hold less value for experienced doctors is challenged. The role of targeted teaching in changing these perceptions should be explored further, both for students and clinicians, who act as role models.